2020
DOI: 10.21873/cgp.20228
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Genetic VDR SNP c.907+75C>T and Prostate Cancer Risk Is Modified by Tanning Potential

Abstract: Background: Prostate cancer (PCa) is a multifactorial disease involving complex interactions between genetic and physiological/environmental factors. Vitamin D receptor (VDR) plays a role in numerous cellular pathways and it has been suggested that VDR genetic variants influence individual susceptibility to PCa. Materials and Methods: Logistic regression analysis was used to assess the association of six VDR single nucleotide polymorphisms (SNPs) and factors such as tanning potential and UV sunlight exposure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A study was done in African Americans where SNP1 and SNP4 in interaction with sun tanning showed 2 and 4 times increased chances of PCa cases respectively whereas SNP5 showed protective outcome by reducing the risk by 5%. Interestingly, among the reported SNPs, SNP2 and SNP6 showed no associations [18]. A genotype study found homologous loci for VDR rs2107301 and rs2238135 showed 2-2.5 times increased chance of risk for PCa [19].…”
Section: Vdr (Vitamin D (1 25-dihydroxyvitamin D3) Receptor)mentioning
confidence: 99%
“…A study was done in African Americans where SNP1 and SNP4 in interaction with sun tanning showed 2 and 4 times increased chances of PCa cases respectively whereas SNP5 showed protective outcome by reducing the risk by 5%. Interestingly, among the reported SNPs, SNP2 and SNP6 showed no associations [18]. A genotype study found homologous loci for VDR rs2107301 and rs2238135 showed 2-2.5 times increased chance of risk for PCa [19].…”
Section: Vdr (Vitamin D (1 25-dihydroxyvitamin D3) Receptor)mentioning
confidence: 99%